Metformin improves diastolic dysfunction of non-diabetic patients with metabolic syndrome: the MET-DIME randomized trial. (14th October 2021) - Santos-Ferreira, D; Ladeiras-Lopes, R; Sampaio, F; Leite, S; Vilela, E; Leite-Moreira, A; Bettencourt, N; Gama, V; Braga, P; Fontes-Carvalho, R
Abstract: Background: Metabolic syndrome (MetS) is a cluster of cardiovascular risk factors, including abdominal obesity, dyslipidaemia, arterial hypertension and abnormal glucose homeostasis, which occur together more frequently than by chance. Diastolic dysfunction (DD) is one of the most frequent manifestations of subclinical cardiac involvement of MetS, ultimately leading to heart failure with preserved ejection fraction. Metformin's new potential therapeutic actions include prevention of cardiac remodeling and fibrosis. Purpose: We aimed to evaluate if metformin improves diastolic function (DF) in non-diabetic patients with MetS. Methods: A prospective, randomized, open-label, blinded-endpoint trial was conducted over 24 months. Fifty-four non-diabetic adults with MetS and DD (defined as mean e'<10.2cm/s or <7.2cm/s for individuals 40–59 and 60–65 years old, respectively) were randomized to lifestyle counseling (control arm) or lifestyle counseling plus metformin (intervention arm) on a target dose of 1000 mg bid (figure 1). The primary endpoint was the change in mean e' velocity, assessed at 6, 12 and 24 months. Secondary endpoints included improvements in insulin resistance (HOMA-IR), functional capacity (peak oxygen uptake – VO2) and QoL (SF-36 score). Linear mixed effects modelling was used for longitudinal data analysis based on modified intention-to-treat (mITT) and per-protocol (PP) approaches. Results: Forty-nine patients (mean age=51.8±6.4; 55% males) were included in the mITT analysis. Metformin use, on top of lifestyle counseling, led to an increase in mean e' velocity during follow-up (figure 2), with results at 24 months of +0.67±1.90cm/s (vs. −0.33±1.50cm/s in the control group, p=0.056), which reached statistical significance in PP analysis (+0.80±1.99cm/s vs. −0.37±1.52cm/s, p=0.039). In a random intercept linear mixed model adjusting for age, gender, treatment with drugs targeting the renin-angiotensin-aldosterone axis, presence of heart failure and baseline degree of DD, both mITT and PP analysis showed a statistically significant improvement of DF with metformin over time (β-coefficient=0.28, standard error (SE)=0.13, p=0.034, and β-coefficient=0.35, SE=0.14, p=0.011, respectively). This effect was independent of the observed reduction in insulin resistance. There were no differences regarding peak VO2 nor SF-36 score. Conclusions: Treatment with metformin of non-diabetic MetS patients with DD, on top of lifestyle counseling, was associated with improved diastolic function. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Merck